2014
DOI: 10.1080/17429145.2014.902125
|View full text |Cite
|
Sign up to set email alerts
|

Role of plant growth-promoting rhizobacteria and their exopolysaccharide in drought tolerance of maize

Abstract: The present study deals with the isolation and characterization of exopolysaccharides (EPS) produced by the plant growth-promoting rhizobacteria (PGPR) from arid and semiarid regions of Pakistan, and to investigate the drought tolerance potential of these PGPR on maize when used as bioinoculant alone and in combination with their respective EPS. Three bacterial strains Proteus penneri (Pp1), Pseudomonas aeruginosa (Pa2), and Alcaligenes faecalis (AF3) were selected as EPS-producing bacteria on the basis of muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
141
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 341 publications
(156 citation statements)
references
References 60 publications
11
141
1
3
Order By: Relevance
“…Similarly, maize plant inoculated with Burkholderia phytofirmans strain PsJN showed significant increase in root biomass by 70 and 58% in Mazurka and Kaleo cultivars of maize (Naveed et al, 2014). The relation between deeper root system drought tolerance has also been observed by other researchers in maize crop (Hund et al, 2011;Naseem and Bano, 2014).…”
Section: Discussionsupporting
confidence: 48%
“…Similarly, maize plant inoculated with Burkholderia phytofirmans strain PsJN showed significant increase in root biomass by 70 and 58% in Mazurka and Kaleo cultivars of maize (Naveed et al, 2014). The relation between deeper root system drought tolerance has also been observed by other researchers in maize crop (Hund et al, 2011;Naseem and Bano, 2014).…”
Section: Discussionsupporting
confidence: 48%
“…Some researchers have revealed that plants exhibit reduced total sugar contents under stress [48]. However, inoculation of growth-promoting bacteria enhance both total sugar and protein contents in metal-stressed plants and help in alleviating relative stress [49][50].…”
Section: Effect Of Bacterial Inoculation On Physiological Traits Of Cmentioning
confidence: 99%
“…Endophytic bacteria can induce tolerance to abiotic stresses such as salinity and drought, while some populations confer tolerance to specific stress factors and are responsible for the survival of plants under these particular environmental conditions (Gond et al, 2015; Montañez et al, 2011). Thus, the microorganisms that establish positive interactions with plant roots play a key role in cropping systems and have promising biotechnological potential to be used in sustainable agriculture.In Mexico there are no studies on endophytic bacterial communities in roots of drought Así mismo, se ha demostrado la eficiencia con la inoculación de estas bacterias en maíz promoviendo tolerancia al stress por sequía (Fan et al, 2015), mediado por el incremento de la longitud y biomasa de la raíz mejorando la absorción de agua y nutrientes (Naseem y Bano, 2014;Yasmin et al, 2013). Las bacterias endófitas pueden inducir tolerancia contra enfermedades abióticas como salinidad y sequía, mientras que algunas poblaciones confieren tolerancia a factores de estrés específico y son responsables de la supervivencia de las plantas bajo esas condiciones particulares del ambiente (Gond et al, 2015; Montañez et al, 2011).…”
unclassified
“…In Mexico there are no studies on endophytic bacterial communities in roots of drought Así mismo, se ha demostrado la eficiencia con la inoculación de estas bacterias en maíz promoviendo tolerancia al stress por sequía (Fan et al, 2015), mediado por el incremento de la longitud y biomasa de la raíz mejorando la absorción de agua y nutrientes (Naseem y Bano, 2014;Yasmin et al, 2013). Las bacterias endófitas pueden inducir tolerancia contra enfermedades abióticas como salinidad y sequía, mientras que algunas poblaciones confieren tolerancia a factores de estrés específico y son responsables de la supervivencia de las plantas bajo esas condiciones particulares del ambiente (Gond et al, 2015; Montañez et al, 2011).…”
unclassified
See 1 more Smart Citation